Assessing Sharia Compliance in the Halal Tourism Industry of Banda Aceh - Jihan Inayah; Nurhasanah; Khaira Nadila; Moses Adeolu Agoi (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2026)
Sharia compliance serves as an instrument for standardizing the measurement of halal-related assessments. However, in both practice and regulation, the halal tourism industry has not given sufficient attention to these indicators. This study aims to analyze the regulatory framework governing halal tourism and to examine the extent to which sharia compliance has been implemented by halal tourism operators in Banda Aceh City. This research employs an empirical-qualitative approach conducted in Banda Aceh City. Data were collected through in-depth interviews and field observations, guided by Banda Aceh City Qanun Number 3 of 2022 on the Implementation of Halal Tourism. The findings indicate that regulations governing the halal industry are stipulated in Banda Aceh City Qanun Number 3 of 2022 on the Implementation of Halal Tourism, which is substantively based on the DSN-MUI Fatwa on halal tourism. In this regard, sharia compliance implemented by tourism operators in Banda Aceh City has conformed to the prevailing regulatory provisions. This research emphasizes that the internalization of Sharia principles in the Halal Tourism Qanun has been maximally absorbed, resulting in safe, comfortable, and sustainable halal tourism practices.